The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1162/jocn_a_01816
|View full text |Cite
|
Sign up to set email alerts
|

Pretrial Theta Band Activity Affects Context-dependent Modulation of Response Inhibition

Abstract: The ability to inhibit a prepotent response is a crucial prerequisite of goal-directed behavior. So far, research on response inhibition has mainly examined these processes when there is little to no cognitive control during the decision to respond. We manipulated the “context” in which response inhibition has to be exerted (i.e., a controlled or an automated context) by combining a Simon task with a go/no-go task and focus on theta-band activity. To investigate the role of “context” in response inhibition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 77 publications
1
30
0
Order By: Relevance
“…On the other hand, a significantly higher overall accuracy in incongruent trials (96.15% ± 0.38) than in congruent trials (94.60% ± 0.48) was found in the Nogo condition ( t = −6.087, p = 0.002). These results were also confirmed by additional Wilcoxon signed-rank tests for Go ( z = −3.049, p = 0.004) and Nogo trials ( z = −5.234, p = 0.002) and align with previous findings using the same experimental paradigm on healthy participants [ 21 , 23 ].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…On the other hand, a significantly higher overall accuracy in incongruent trials (96.15% ± 0.38) than in congruent trials (94.60% ± 0.48) was found in the Nogo condition ( t = −6.087, p = 0.002). These results were also confirmed by additional Wilcoxon signed-rank tests for Go ( z = −3.049, p = 0.004) and Nogo trials ( z = −5.234, p = 0.002) and align with previous findings using the same experimental paradigm on healthy participants [ 21 , 23 ].…”
Section: Resultssupporting
confidence: 89%
“…To measure the effect of automatic vs. controlled processes on response inhibition, an integration of Simon and Go/Nogo paradigms was used ( Figure 1 ) [ 22 , 23 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In incongruent Simon trials, the automatic and controlled routes are activated and induce a conflict (Chmielewski & Beste, 2017 ; Hommel, 2011 ; Keye et al, 2013 ), which increases the contribution of controlled response selection processes. Using a Simon‐Go/Nogo task, it has been shown that there is a lower rate of false alarms (i.e., erroneous responses in Nogo trials) when a Nogo stimulus is embedded in incongruent than congruent Simon task trials (Chmielewski et al, 2018 ; Chmielewski et al, 2020 ; Chmielewski & Beste, 2017 ; Opitz et al, 2019 ; Wendiggensen et al, 2022 ). Previous studies investigated the neural dynamics underlying the interplay of automatic and controlled processes during response inhibition (Chmielewski et al, 2018 ; Chmielewski et al, 2020 ; Chmielewski & Beste, 2017 ; Opitz et al, 2019 ; Wendiggensen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%